Impacts of the COVID-19 Pandemic on Elementary School Teachers’ Practices and Perceptions Across the Spring and Fall 2020 Semesters - Goodrich, J. Marc; Hebert, Michael; Namkung, Jessica M. (Frontiers in Education, 2022)
Following the closure of schools in the spring 2020 semester due to the COVID-19 pandemic, we conducted two surveys to understand how the pandemic affected elementary education in the U.S. First, we conducted a survey at the end of the spring 2020 semester to understand how school closures impacted delivery of instruction. Second, we conducted a follow up survey in November 2020 to determine the nature of instruction provided to students when schools did or did not re-open in Fall 2020 and understand teachers’ perceptions of student learning and achievement during the pandemic. Each survey was sent to a random sample of over 9,000 teachers who were randomly sampled to be representative of the population of the U.S. Results indicated that many students did not receive direct instruction in academics skills during the spring 2020 semester. Although by late fall 2020 teachers reported broad use of some form of in-person instructional model, teachers indicated that many of their students were not ready to transition to the next grade level and that achievement gaps were larger in fall 2020 than in typical years. These findings have important implications for practices during potential school closures in the future.